Pengaruh Kepercayaan dan Kemudahan terhadap Keputusan Pembelian Menggunakan Metode Pembayaran Shopeepay di Kota Palembang - Ummi Rani Syafitri; Ahmad Maulana; Aslamia Rosa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
E-commerce is an online channel that can be reached by a person through computer services and is used by business people in carrying out their business activities, e-commerce can also be used by consumers to obtain information using the help of smart phones by providing information services to consumers in making choices. In the development of the era, humans will always follow developments, such as in electronic money such as Shoopepay which is used in various transactions. This research discusses the people of Palembang city in using e-wallet shoopepay as seen from the convenience and trust in purchasing decisions, with the primary method or by observation or questionnaire distribution interviews of 100 respondents where the results will be collected then analyzed using multiple linear regression analysis techniques. The results of this study showed that as many as 15 question indicators were declared valid. Besides that, the variables of trust and convenience have a significant influence on purchasing decisions in a positive direction, this means that the people of Palembang city will increase purchases based on the convenience and trust provided by the application/electronic wallet, the Shoopepay e-wallet.